Odpowiedzi

2009-10-08T16:54:54+02:00
E) (³√54 + ³√81) ( √18 - √2)²
________________
8 ³√2 + 8 ³√3

(3³√2+3³√3)(18-12+2)
---------------------------=
8 ³√2 + 8 ³√3
3(³√2+³√3)(18-12+2)
---------------------------=
8 (³√2 + ³√3 )


=3



d) √1,21 + 5 ³√0,008 - √4,41
_________________________
√13


1,1 + 5*0,2 -2,1
--------------------=
√13

0
2009-10-08T17:05:20+02:00
E) (³√54 + ³√81) ( √18 - √2)²
________________________ =
8 ³√2 + 8 ³√3

=[(3∛2+3∛3)(18-12+2)]/[8 ³√2 + 8 ³√3] = 3/8(∛2+∛3)*8=3(∛2+∛3)

d) √1,21 + 5 ³√0,008 - √4,41
_________________________ =
√13

=[1,1+5*0,1-2,1]/√13 = -0,5/√13=-0,5√13/13